THE APPLICATION OF SWAN IDEA SOURCE ON BRIDAL FASHION - Ningrum, Vinna Kumala; Russanti, Irma (Universitas Negeri Yogyakarta, 2024)
Swans are the most loyal animals that only mate once in a lifetime. The purpose of this research is to find out the process of making and the finished result of bridal fashion with a swan as the source of the idea. This research method uses a three-stage design process approach. This method consists of three stages of research: problem definition and research, creative exploration and implementation. The design direction was determined in the initial stage, and in the second stage, a moodboard was made. The implementation stage involves applying a swan feather and manipulating fabric decoration as the centre of attention on the bridal outfit. The process of manipulating fabric starts with preparing copper wire, segment fabric and brocade fabric, then cutting to form strands of swan feathers and sewn with balut stitch on all sides to unite the three materials. The results of this research show bridal fashion with feather-shaped manipulating fabric decoration, with two designs of men's and women's bridal fashion. The final result is the style of Muslim clothing, according to the provisions of Islamic law, intended to cover parts of the body that are inappropriate to be shown to the public. The primary material is tille sequins and satin maxmara lining with the appropriate size, but it does not show the shape of the woman's body so that it can be worn for Muslim women wearing hijab.